2023
DOI: 10.3390/land12030624
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Boosts Prospects for Recovery of Rural Tourism in Serbia

Abstract: Rural tourism in Serbia had its chance to shine with the advent of the COVID-19 pandemic. The aim of this study was to determine to what extent the quality of rural service can contribute to improving rural tourism, and predictions for the continuation of the trend in terms of increasing the number of overnight stays in rural households. The obtained results show a small number of services in the sector could be improved, but that all elements except price value can influence the future development of rural to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…The current study proved that the experience economy directly influences customer behavior, which differs from their study. The result of the relationship between the experience economy and wordof-mouth intentions also can be supported by existing tourism studies (e.g., [59,60]).…”
Section: Theoretical Implicationssupporting
confidence: 67%
See 1 more Smart Citation
“…The current study proved that the experience economy directly influences customer behavior, which differs from their study. The result of the relationship between the experience economy and wordof-mouth intentions also can be supported by existing tourism studies (e.g., [59,60]).…”
Section: Theoretical Implicationssupporting
confidence: 67%
“…Tourists' experiences regarding functional, satisfactory, and emotional elements can positively boost the future prediction of tourism development [59]. Gajić et al [60] empirically proved that high-quality tourist service experiences directly form tourists' loyalty to the destination.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Technological and digital innovations are changing the way people live, work, travel, and communicate with each other and how they spend their free time, but the boundaries between digital, social, physical and environmental environments are increasingly intertwined [107]. Environmental risks have the potential to affect the natural environment, but also the social environment in terms of influencing the behavior of tourists in choosing tourist destinations.…”
Section: Discussionmentioning
confidence: 99%
“…These areas, with their high levels of natural features, have brought economic benefits to local communities. Gajić et al found that mountain rural settlements in Serbia could establish a barrier against COVID-19 by developing tourism [162]. However, due to the limited capacity of mountain ecosystems, excessive economic activities such as mountain tourism are subject to government regulation and restrictions [163].…”
Section: Research Trend In Factors Of Features and Characteristics Ba...mentioning
confidence: 99%